2013
DOI: 10.1111/php.12128
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Retinoic Acid Radical Cation with Lysozyme and Antioxidants: Laser Flash Photolysis Study in Microemulsion

Abstract: All-trans retinoic acid (ATRA) plays essential roles in the normal biological processes and the treatment of cancer and skin diseases. Considering its photosensitive property, many studies have been focused on the photochemistry of ATRA. In this study, we investigated the transient phenomena in the laser flash photolysis (LFP) of ATRA in microemulsion to further understand the photochemistry of ATRA. Results show that 355 nm LFP of ATRA in both acidic and alkaline conditions leads to the generation of retinoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
(74 reference statements)
1
10
0
Order By: Relevance
“…It may be speculated that the extracted electron stems from the endocyclic double bond, similar to the case of retinoic acid. 37,38 At the low temperature of the experiment the cationic state may be stabilized by a concomitant change of the molecular geometry. A closely related mechanism has been reported from charged metal atoms on insulators.…”
Section: Generation Of Spin In Single Cholesterol Molecules On Goldmentioning
confidence: 99%
“…It may be speculated that the extracted electron stems from the endocyclic double bond, similar to the case of retinoic acid. 37,38 At the low temperature of the experiment the cationic state may be stabilized by a concomitant change of the molecular geometry. A closely related mechanism has been reported from charged metal atoms on insulators.…”
Section: Generation Of Spin In Single Cholesterol Molecules On Goldmentioning
confidence: 99%
“…Furthermore, it has been also demonstrated that α-tocopherol can reduce, and thereby recycle, the semi-oxidized forms of other antioxidants, including cation radicals of two forms of vitamin A: retinol and retinoic acid [11,12,13]. Retinoid cation radicals can be formed as a result of the interaction of retinoids with hydroxyl radicals, peroxyl radicals, such as trichloromethylperoxyl radical, or the photoionization of retinoids by exposure to ultraviolet light [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cation radicals of retinol and retinoic acid can damage important biomolecules, such as certain amino acids and proteins [12,13]. It has been also shown that α-tocopherol has the potential to act as an antioxidant, protecting the amino acids from oxidation by the retinol cation radical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Hence, the antioxidant capacities of compounds 38c and 40c were studied using DPPH and ABTS, assays rst. In fact, VC and GA have been used as a standard antioxidant in the performed experiments, 37,38 According to the data obtained from the present study, it was found that compounds 38c and 40c showed good scavenging activity against DPPH and ABTS free radicals, and suggested that both of compounds 38c and 40c had good antioxidant activity. Testing compound inhibition cell proliferation method is a common method to indicate the toxicity of a compound.…”
Section: Discussionmentioning
confidence: 53%